Simple thrombin-based method for eliminating fibrinogen interference in serum protein electrophoresis of haemodialysed patients - Rade, Anamarija (Array, 2020)
Introduction: Serum samples of haemodialysed patients collected through vascular access devices, e.g. central venous catheter (CVC) can contain residual heparin, which can cause incomplete clotting and consequently fibrinogen interference in serum protein electrophoresis (SPE). We hypothesized that this problem may be overcome by addition of thrombin and aimed to find a simple thrombin-based method for fibrinogen interference removal. Materials and methods: Blood samples of 51 haemodialysed patients with CVC were drawn through catheter into Clot Activator Tube (CAT) and Rapid Serum Tube Thrombin (RST) vacutainers (Becton Dickinson, New Jersey, USA) following the routine hospital protocols and analysed with gel-electrophoresis (Sebia, Lisses, France). Samples were redrawn in the CAT tubes and re-analysed after being treated with thrombin using two methods: transferring CAT serum into RST vacutainer and treatment of CAT serum with fibrinogen reagent (Multifibren U, Siemens, Marburg, Germany). Results: Direct blood collection in RST proved to be slightly more efficient than CAT in removing the interfering band in beta fraction (CAT removed 6/51 and RST removed 12/51, P = 0.031). Transferring CAT serum into the RST vacutainer proved to be more efficient for subsequent removal of interfering band from CAT serum than the addition of fibrinogen reagent (39/45 vs. 0/45 samples with efficiently removed interfering band, P <0.001). Conclusion: Fibrinogen interference caused by incomplete clotting because of residual heparin can be overcome by addition of thrombin. Transferring CAT serum into the RST vacutainer was the most efficient method.